ASSESSMENT OF NOISE FROM DIESEL GENERATORS USED IN GSM BASE STATIONS IN KANO METROPOLIS, NIGERIA. (FUDMA JOURNAL OF SCIENCES, 2020)
In Nigeria, most telecommunication companies use diesel generators to power their Base Transceivers Stations (BTS) due to erratic power supply to avoid failure in transmission of their services. This has resulted to noise pollution to man and the environment. This study investigated the compliance BTS in Kano Metropolis with the NESREA permissible limits. Twenty BTS were randomly selected and the sampling was carried out over a period of 5 days. For each of the Base Stations, three sampling points were established. Sampling was carried out at point source, 5m and 10m away from point source. Measurement of the Daytime and Night time noise levels and survey questionnaires were used to assess the socio-economic impacts of the generators on health and environment. The average noise levels of the BTSs measured ranged from 66.1dB–87.9dB for Daytime and 64.9dB–84.3dB for Night time which showed that the measured noise levels at the 20 stations in all the sampling points were above the NESREA limit of 55dB for Day Time and 45dB for Night Time. Findings from the survey analysis revealed that over 90% of the participants felt the surroundings of the Base Stations were not comfortable. Due to the health implications of the observed high noise levels and vibration from the Base Stations, it is recommended that NESREA should review the 10m setback by increasing the distance for base stations that will be sited in the future to avoid any threat to health. Adoption of environmentally friendly power sources was also recommended.
Keywords: GSM, Base Stations, NESREA, Power Sources